2020
DOI: 10.1111/1365-2656.13208
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of amphibian population dynamics and asynchrony at local and regional scales

Abstract: 1. Identifying the drivers of population fluctuations in spatially distinct populations remains a significant challenge for ecologists. Whereas regional climatic factors may generate population synchrony (i.e. the Moran effect), local factors including the level of density dependence may reduce the level of synchrony. Although divergences in the scaling of population synchrony and spatial environmental variation have been observed, the regulatory factors that underlie such mismatches are poorly understood. Few… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 78 publications
(101 reference statements)
0
16
0
1
Order By: Relevance
“…Spatial variation in density dependence is also known to decrease the effect of environmental stochasticity on population synchrony (Cayuela et al., 2020; Hugueny, 2006; Liebhold et al., 2006; Peltonen et al., 2002). For example, Peltonen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spatial variation in density dependence is also known to decrease the effect of environmental stochasticity on population synchrony (Cayuela et al., 2020; Hugueny, 2006; Liebhold et al., 2006; Peltonen et al., 2002). For example, Peltonen et al.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any relationship between synchrony of A. lacustris and of its most consumed prey species, which may favor the hypothesis of a shared environmental effect. Spatial variation in density dependence is also known to decrease the effect of environmental stochasticity on population synchrony (Cayuela et al, 2020;Hugueny, 2006;Liebhold et al, 2006;Peltonen et al, 2002). For example, Peltonen et al (2002) found that the mismatch between population synchrony and environmental synchrony in gypsy moth (in terms of their distance decays) could be attributed to geographic differences in density dependence among local populations.…”
Section: Mechanisms Of Spatial Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…Бесхвостые амфибии относятся к холоднокровным позвоночным и поэтому наиболее чувствительны к климатическим изменениям (Маслова, 2006;Beebee, 1995;Grant et al, 2020;Green et al, 2020). Глобальное потепление сопровождается значимой трансформацией локальных погодно-климатических условий, которые оказывают влияние на факторы, существенные для популяций амфибий (Cayuela et al, 2020). К наиболее важным явлениям, очевидно, следует отнести фенологические сдвиги репродукции, а также изменение водности нерестовых водоёмов, иногда приводящие к их полной деградации (Ермохин, Табачишин, 2018 а;Yermokhin et al, 2017.…”
Section: поволжский экологический журнал № 1 2021unclassified
“…Population‐level responses to large‐scale disturbance and stress can be spatially heterogeneous if local habitat conditions or connectivity vary across a landscape (Patrick et al, 2021). In such cases, large‐scale environmental controls may be locally attenuated or exacerbated, allowing for a diversity of biological responses depending on local conditions (Bunnell et al, 2010; Cayuela et al, 2020; Hansen et al, 2019). Such diverse responses are key to preserving asynchronous dynamics and ecological rescue, that is, the capacity of colonists from thriving populations to repopulate impacted ones through dispersal (Brown & Kodric‐Brown, 1977; Hammond et al, 2020).…”
Section: Introductionmentioning
confidence: 99%